Supervisor and Co-worker Support and Work Engagement: The Role of Teachers’ Workload - Indra Wijaya (Faculty of Psychology, Universitas Surabaya, 2014)
The aim of this study was to examine the relationship between teachers’ work engagement and support from supervisors and co-workers, as well as to investigate the role of the work- load as a moderator. The participants (N = 118) were selected using a convenience sampling method from three private schools in Surabaya. Data were collected using a questionnaire with five response choices and were analyzed using SPSS 19.0, specifically multiple regression analysis and test of absolute value difference. The results showed that: (a) supervisor and co- worker support were simultaneuously positively related to work engagement (r = .432, p < .05), (b) supervisor support were not statistically significant correlated to work engagement (r = .135, p > .05), (c) co-worker support were positively correlated statistically significant to work engage- ment ( r = .425 , p < .05 ), (d) workload moderated the relationship between supervisor support and work engagement (r = .325 , p < .05), (e) workload moderated the relationship between co-worker support and work engagement (r = .199 , p < .05). These results highlighted the importance of supervisor and co-worker support in predicting teachers’ engagement, moderated by the teachers’ workload. Tujuan studi ini adalah untuk menguji hubungan antara dukungan sosial atasan dan rekan kerja, dan keterikatan kerja, serta untuk menguji fungsi beban kerja sebagai moderator. Subjek (N = 118) adalah para guru yang diperoleh melalui convenience sampling. Data diperoleh menggunakan skala pernyataan tertutup dengan lima pilihan jawaban, yang di- analisis menggunakan uji analisis regresi berganda dan uji nilai selisih mutlak pada SPSS 19.0. Hasil menunjukkan: ada hubungan antara dukungan sosial atasan dan rekan kerja secara simultan terhadap keterikatan kerja (r = .432; p < .05), tidak ada hubungan dukungan sosial atasan dan keterikatan kerja (r = .135; p > .05), ada hubungan dukungan sosial rekan kerja dan keterikatan kerja (r = .425; p < .05). Terdapat hubungan antara dukungan sosial atasan dan keterikatan kerja, dengan beban kerja sebagai variabel moderator (r = .325; p < .05), dan ada hubungan antara dukungan sosial rekan kerja dan keterikatan kerja, dengan beban kerja sebagai variabel moderator (r = .199; p < .05). Disimpulkan bahwa dukungan sosial atasan dan rekan kerja merupakan aspek-aspek penting dalam menumbuhkan keterikatan kerja guru yang dimoderatori beban kerja